Mesalazine solubility in supercritical carbon dioxide with and without cosolvent and modeling - Seyed Ali Sajadian; Nadia Esfandiari; Adrián Rojas; Salar Hemmati; Abolghasem Jouyban; Gonzalo Aguila; Chandrasekhar Garlapati (Scientific Reports)
Abstract In this study, the solubility of mesalazine in supercritical carbon dioxide with and without cosolvent was carried out for the first time at different temperatures and pressure values ranging from 308 to 338 K and 12 to 30 MPa, respectively. The determined experimental molar solubilities of mesalazine in supercritical carbon dioxide were in the range of 4.41 × 10–5 to 9.97 × 10–5 (308 K), 3.9 × 10–5 to 13.1 × 10–5 (318 K), 3.4 × 10–5 to 16 × 10–5 (328 K) and 3.3 × 10–5 to 18.4 × 10–5 (338 K). Meanwhile, the determined experimental molar solubilities in supercritical carbon dioxide using 2% dimethyl sulfoxide as cosolvent were in the range of 28.22 × 10–5 to 36.2 × 10–5 (308 K), 26.07 × 10–5 to 51.41 × 10–5 (318 K), 25.02 × 10–5 to 69.07 × 10–5 (328 K) and 25.86 × 10–5 to 82.6 × 10–5 (338 K). A novel association model was employed to simulate the solubility data of the binary and ternary systems. Various semiempirical correlations were utilized to calculate the solubility of mesalazine in supercritical carbon dioxide. The new association model was deemed the most superior model, achieving an average absolute relative deviation value of 4.13% without a cosolvent, and 3.36% when a cosolvent was included.